2015 Transducers - 2015 18th International Conference on Solid-State Sensors, Actuators and Microsystems (TRANSDUCERS) 2015
DOI: 10.1109/transducers.2015.7181025
|View full text |Cite
|
Sign up to set email alerts
|

Flexible composite thermal energy harvester using piezoelectric PVDF polymer and shape memory alloy

Abstract: A novel flexible composite thermal energy harvester is presented, which couples pyroelectric and piezoelectric effects of polyvinylidene fluoride (PVDF) with shape memory effect of a TiNiCu alloy. The harvester combines superior flexibility of PVDF with large temperature-induced strain of the shape memory alloy (SMA) to harvest small and quasi-static temperature variations. The composite with a volume of 27.5 mm 3 (post-stamp size) can harvest an energy density of 0.41 mJ/cm 3 per event, i.e. a temperature var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The power management circuit is shown in Figure 4a, comprising a switch that commutes when the PVDF capacitor is fully charged [1]. Component references are: (D) diode MURS120G3T, (L) inductor MSS1210-105KED Coilcraft (1 mH), and (C) capacitor VJ0805Y472KXCAC-Vishay (20 nF).…”
Section: Circuit Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The power management circuit is shown in Figure 4a, comprising a switch that commutes when the PVDF capacitor is fully charged [1]. Component references are: (D) diode MURS120G3T, (L) inductor MSS1210-105KED Coilcraft (1 mH), and (C) capacitor VJ0805Y472KXCAC-Vishay (20 nF).…”
Section: Circuit Modelmentioning
confidence: 99%
“…Recent results showed that PVDF composite harvesters are able to harvest DC-energy from thermal fluctuations or small temperature changes when coupled with shape memory materials (SMA) [1]. A power conversion circuit is connected to the harvester by a switch (thermal).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations